New data on the practice of desertions from the Red (Soviet) Army as an expression of the anti-Soviet resistance of the Moldavian SSR population in the years 1944-1954 - Anatolie LEȘCU (Bulletin of "Carol I" National Defense University)
The history of the eastern part of what used to be Moldova, or the eastern area of Romanian territory located in the Pruto-Nistrean interfluve, which later became known as Bessarabia, is a tragic and turbulent one. In the last 200 years alone, this territory has undergone three occupations and annexations, all carried out by the Russian state in different forms: 1812, 1940, and 1944. The Sovietization of Moldova after the subsequent occupation of Bessarabia in the summer of 1944 proceeded with great difficulties, as the artificially created population of the Moldavian SSR resisted Soviet authorities in various ways. One of the forms of resistance was desertion from the Soviet Army. Desertion, a phenomenon characteristic of all armies worldwide, is a criminal offence that involves evading military service through various methods, such as fleeing from a unit or avoiding enlistment altogether. Under the conditions of forced Sovietization in the SSR between 1944 and 1953, this practice took on distinctly anti-Soviet characteristics, becoming a part of the population’s struggle against the occupiers.